Expanding HIVAIDS prevention programmes through Safe Male Circumcision and Voluntary Counselling and Testing in Uganda - Ahaibwe, Gemma; Kasirye, Ibrahim; Barungi, Mildred (My University, 2013)
Although Uganda initially registered large reductions in HIV/AIDS prevalence rate during the 1990s, the rate of new HIV infection is on the rise across the country. At least 1.2 million Ugandans are infected with the HIV virus1 . Recent evidence from the 2011 Uganda AIDS Indicator Survey revealed that the HIV/AIDS prevalence rate had increased from 6.4 percent in 2004/5 to 7.3 percent by 20112. The trends in new HIV infections in figure 1 suggest that the annual number of new HIV infections increased by 11.4 percent from 115,775 in 2007/08 to 128,980 in 2010/11, despite the huge amounts of resources earmarked for HIV/AIDS related expenditures. The increase in the HIV/AIDS prevalence has been blamed on the complacency of Ugandans with the availability of anti-retrovaral therapies (ARTs)— especially regarding sexual behavior.